Prevalence of Helicobacter pylori in Human in Dhamar Governorate / Yemen - Almashhadany, Dhary Alewy; Mayass, Sarah Mohammed (Journal of medical and pharmaceutical sciences, 2018)
The present study was conducted to determine the existence and spread of H. pylori among different ages of human. Four hundred and twelve (412) were collected included 206Blood samples and 206 Stool samples from the same patients. This samples were collected from General Thamar Hospital and some private medical laboratories. The results revealed that the prevalence of H.pylori antibody in human blood samples were (82.52%), while the prevalence of H.pylori in stool according to H.pylori antigen test were (18.45%) . The relationship between prevalence of H.pylori antibody and sex, revealed that the females were more exposed to infection with H.pylori, the rate of infection were (85.71%), compared with males infection rate were (76.71%) . Also the relationship between prevalence of H.pylori antigen and sex, confirmed that the rate was (19.55%) from females and (16.44%) from male . This study showed that the high prevalence rate of H.pylori antibody in the blood of children was between the ages of one month to five years (74. 19%), whereas the high prevalence rate of H.pylori antibody in the blood of adult was between the ages of thirty six to forty five years(95.45%).While the high Prevalence rate of H.pylori antigen in the stool of children was between the ages of eleven to fifteen years (28.57%), whereas the high prevalence rate of H.pylori antigen in the stool of adult was between the ages of forty six to fifty five years (25.00%) . The relationship between months and prevalence of H.pylori antibody during period of study indicated that, March and September take the more prevalence rate (100%), but the rate were decreased during the other months .While when we study the relationship between months and prevalence of H.pylori antigen . The highest rate of prevalence of H.pylori antigen were found in February (40.00%), but the rate of prevalence were seen decrease whenever moved away from this month .From this study we concluded that the prevalence of H. pylori among human in Dhamar Governorate was high, and the infection occurred at early years of life.